Quelle éducation morale et civique à l’école ? Pourquoi et comment la mettre en œuvre ? - Gérard Pithon (Éducation et Socialisation)
Moral and civic education in France has known extensions or reductions in schools, with various appellations according to the different governments but also social crises that the country went through since Jules Ferry’s laws on public schools. This education serves as a "pedagogical lever" to improve the "living together" threatened by these crises, and most recently by terrorist attacks claimed by a fundamentalist Islamism. The recommendations of the European Union to its member states underline the importance of relational, intercultural and empathic competences as facilitating elements to live together. In the same spirit, France has established a "common referential of knowledge, skills and culture". These European and national orientations, based on a competency-based approach, are ambitious but remain difficult to implement concretely in the classrooms. However, this article presents some researches, by way of illustration, which fosters mutual aid and cooperation between pupils.